Discourse on ‘Falsity’ in Heritage Revitalization: The Beautification of Kali Besar Jakarta and Its Impacts on Historic Urban Landscape (HUL) - Euis Puspita Dewi; Kemas Ridwan Kurniawan (International Journal of Built Environment and Scientific Research, 2019)
This paper aims to raise the issue of "falsity" in Heritage Revitalization and how it impacts on values in Historic Urban Landscape. The object of the study is the process of revitalization carried out in Kali Besar in the Jakarta Old City Area based on Jakarta Governor's Instruction 2016, No. 101. To evaluate Kali Besar's revitalization planning, this study uses historical methods, especially those relating to aspects of urban space, social and revitalization policies. This study results the findings that the Revitalization of Kali Besar was not done through a good management plan and arranged with various changes as the cause. Beautification is still considered as the main foundation in the Kali Besar arrangement. Historic Urban Landscape must be the main references in the process of revitalizing the Kali Besar area and to produce a mature management plan.